Obstacles of applying human resources accounting in North African countries: A comparative study between Algeria, Tunisia, and Morocco - Ismail SEBTI; Imane BENSIRADJ (Journal of North African Economies, 2025)
This study aims at shedding light on the concept of human resources accounting HRA, its horizons, and obstacles in the economic institutions due to the special costs that give it an accounting particularity in processing the assets. In this frame, we shall focus on the obstacles of the application of HRA in North African countries through a field study conducted on a group of companies working in North Africa. To reach the study objectives, we relied on the analytical descriptive method and a questionnaire for data collection. The study sample included 90 members. We used SPSS for data analysis with reliance on arithmetic means and the other statistical styles. Findings show that: there is no consensus about the accounting processing of HR under study. Moreover, there are obstacles that face the application of HRA in North Africa. In the end, the study recommends a deep focus on the obstacles of the application of HRA in the under study companies in particular in order to reach high efficiency and effectiveness in HRA in the North African companies in general.